2012
DOI: 10.1111/dme.12005
|View full text |Cite
|
Sign up to set email alerts
|

Skin autofluorescence and risk of micro‐ and macrovascular complications in patients with Type 2 diabetes mellitus—a multi‐centre study

Abstract: This study confirms that skin autofluorescence is increased in patients with Type 2 diabetes in a secondary care setting. Skin autofluorescence was associated with macrovascular complications in patients with diabetes and this association was independent of classical risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 15 publications
9
52
0
Order By: Relevance
“…The dissociation of SAF from conventional CVD risk predictors like sex, hypertension and dyslipidemia has previously been found in diabetes mellitus and renal failure (CKD III), but so far no data were available on SAF levels, and changes over time in the current intermediate CVD risk group of primary care overweight persons without diabetes or renal failure [9,15,29]. This dissociation with the aforementioned risk factors extends to persons with CVD and is also confirmed in the current study [23].…”
Section: Discussionsupporting
confidence: 85%
“…The dissociation of SAF from conventional CVD risk predictors like sex, hypertension and dyslipidemia has previously been found in diabetes mellitus and renal failure (CKD III), but so far no data were available on SAF levels, and changes over time in the current intermediate CVD risk group of primary care overweight persons without diabetes or renal failure [9,15,29]. This dissociation with the aforementioned risk factors extends to persons with CVD and is also confirmed in the current study [23].…”
Section: Discussionsupporting
confidence: 85%
“…The UKPDS risk score was studied in people with newly diagnosed Type 2 diabetes without any cardiovascular history and in a relatively young group with a mean age of 52 years; this contrasted with our older group with a mean age of 69 years. It was suggested that SAF can also be strongly influenced by renal status [2]. None of the diabetologists from the five hospitals participating in this study use the UKPDS risk score anymore.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32] In diabetic patients, sAF was described as a marker of chronic hyperglycemia for a longer lifetime period than HbA1c and was also independently associated with micro-and macrovascular complications. 27,30,52 In nondiabetic patients, increased sAF was also associated with increased arterial stiffness, peripheral arterial disease, and coronary artery calcifications. 23,25,37 sAF was also associated with brain atrophy using magnetic resonance imaging, impaired cognitive functions, or some neurologic diseases.…”
Section: Discussionmentioning
confidence: 99%